A Critical Review of Self-Efficacy Theory and Its Relevance to Tawakkal and Ikhlas in Islamic Religious Education - Muhammad Yusron Maulana El-Yunusi; Achmad Defri Juliansyah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This literature study aims to critically analyze Albert Bandura’s theory of self-efficacy from an Islamic perspective and to examine its integration with the concepts of tawakkal (trust in God) and sincerity (ikhlas) in Islamic Religious Education. Using a qualitative library research approach with critical analysis, this study synthesizes concepts from psychological literature and Islamic sources, the findings indicate that self-efficacy theory is relevant to the Islamic concept of tawakkal in emphasizing the importance of belief in driving effort. However, there are fundamental differences in the source and object of that belief. Self-efficacy is derived from empirical experience and focuses on personal ability, whereas tawakkal is rooted in faith and centers on reliance upon Allah, the integration of self-efficacy with tawakkal and sincerity in Islamic education can be achieved through instructional design that develops students’ confidence in their abilities as gifts from Allah, instills awareness that success ultimately comes from Allah thereby fostering gratitude frames failure with patience and tawakkul, and purifies learning intentions solely for the sake of Allah.